Interaction of CTLA-4 with AP50, a clathrin-coated pit adaptor protein - Zhang, Yi (The National Academy of Sciences of the USA, 1997)
CTLA-4 plays a critical role in regulating the immune response. It is mainly located in cytoplasmic vesicles and is expressed only transiently on the surface after T cell activation. In this study, we demonstrate that CTLA-4 is associated with AP50, the medium chain of the clathrin-associated coated pit adaptor protein complex AP2. In a yeast two-hybrid screen, three individual cDNA clones that encode mouse AP50 were isolated, all of which can interact specifically with the cytoplasmic domain of mouse CTLA-4, but not with the cytoplasmic domain of mouse CD28. We have shown that CTLA-4 can bind specifically to AP50 when CTLA-4 and AP50 are cotransfected into human 293T cells. A Y(201) to F(201) mutation in the YVKM intracellular localization motif of the CTLA-4 cytoplasmic domain significantly diminished its binding to AP50. We also found that AP50 bound to a CTLA-4 peptide containing unphosphorylated Y(201) but not to a peptide containing phosphorylated Y(201). Conversely, the p85 subunit of phosphatidylinositol 3-kinase and, to a lesser extent, protein tyrosine phosphatase SYP (SHP-2) and SHP (SHP-1) bind only to the CTLA-4 peptide containing phosphorylated Y(201). Therefore, the phosphorylation status of Y(201) in the CTLA-4 cytoplasmic domain determines the binding specificity of CTLA-4. These results suggest that AP50 and the coated pit adaptor complex AP2 may play an important role in regulating the intracellular trafficking and function of CTLA-4.